Digital Entrepreneurship Education and Mentoring for PGRI Gumelar High School Students to Enhance Entrepreneurial Skills in International Markets Using Digital Media - Purwono Purwono; Khoirun Nisa; Jatmiko Indriyanto; Lutviana; Dimas Febri Kuncoro (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
The development of information technology continues to increase and has reached all levels of society, including the younger generation. This generation is present as a cohort with superior personalities and the ability to comprehend knowledge and technology, enabling them to compete locally and globally. Technological advancements also catalyze innovations, fostering creativity in the economic and business fields. SMA PGRI Gumelar is a private school in Gumelar District, Banyumas Regency, which offers various life skill activities such as graphic design, foreign languages, photography, videography, and more. However, the existing activities have not yet yielded works that can be marketed internationally. This service aims to optimize graphic design life skills training for students so that they can produce work that is marketable on overseas platforms, namely Envato. This marketplace has specific standards for works that will be sold; therefore, education and assistance are provided to enhance motivation for digital media-based entrepreneurship in the international market. This beginner community service activity will be conducted from July to October 2023 at SMA PGRI Gumelar. The outcome of this activity will be graphic design work ready to be uploaded to the Envato marketplace. Based on the results of the questionnaire distributed to participants, there was an increase in motivation as a designpreneur, increasing by 35%, Figma skills increasing by 45% and Photoshop skills increasing by 35%. Another output of this project is a graphic design tutorial book with an ISBN number